Analyzing the temperature dependence of titania photocatalysis: kinetic competition between water oxidation catalysis and back electron–hole recombination - Cho,Y; He,T; Moss,B; Benetti,D; Liang,C; Tian,L; Hart,LJF; Wilson,AA; Taniguchi,Y; Cui,J; Yang,M; Eslava,S; et al. (ACS Catalysis, 2024)
This study examines the kinetic origins of the temperature dependence of photoelectrochemical water oxidation on nanostructured titania photoanodes. We observe that the photocurrent is enhanced at 50 °C relative to 20 °C, with this enhancement being most pronounced (by up to 70%) at low anodic potentials (<+0.6 V vs RHE). Over this low potential range, the photocurrent magnitude is largely determined by kinetic competition between water oxidation catalysis (WOC) and recombination between surface holes and bulk electrons (back electron–hole recombination, BER). We quantify the BER process by transient photocurrent analyses under pulsed irradiation. Remarkably, we find that the kinetics of BER (∼90 ms half-time) are independent of temperature. In contrast, the kinetics of WOC, determined from the analysis of the photoinduced absorption of accumulated surface holes, are found to accelerate up to 2-fold at 50 °C relative to 20 °C. We conclude that the enhanced photocurrent densities observed in the low-applied potential region result primarily from the accelerated WOC, reducing losses due to the competing BER pathway. At higher applied potentials (>+0.6 V vs RHE), a smaller (∼10%) enhancement in photocurrent density is observed at 50 °C relative to 20 °C. Photoinduced absorption studies, correlated with studies using triethanolamine as a hole scavenger, indicate that this more modest enhancement at anodic potentials primarily results from an enhanced charge separation efficiency. We conclude by discussing the implications of these results for the practical application of photoanodic WOC under solar irradiation, influenced by these temperature-independent and -dependent underlying kinetic processes.